Manajemen Edukasi Keperawatan untuk Pencegahan Konsumsi Jajanan Berisiko pada Anak Sekolah Dasar - Siregar, Miftahul Khoiriyah; Pane, Nikmah Kemala Sari; Almadany, Ulfah Hidayah; Edy Sujoko (Universitas Aufa Royhan Di Kota Padangsidipuan, 2025)
Unhealthy eating habits among elementary school children pose a serious risk to their long-term physical and mental development. In Indonesia, the consumption of snacks high in sugar, preservatives, and harmful additives remains prevalent. This community service program aimed to increase nutritional awareness and improve students’ behavior toward healthy snacking. The activity was conducted at SD Negeri 200204 Kampung Losu, involving students, teachers, parents, and canteen managers. Methods included nutrition education sessions, demonstrations of healthy snack preparation, simulated healthy canteen activities, and training for teachers and parents. The results showed a significant increase in students' knowledge, with 68% reporting changes in behavior such as bringing healthy food from home and avoiding unhealthy snacks. The school also implemented a canteen policy to sell only healthy snacks. Active involvement from parents and teachers contributed to the program’s success. This program effectively enhanced health awareness among children and stakeholders and serves as a model for school-based health promotion initiatives.